Numerical Investigation on Stress Intensity Factor and J Integral in Friction Stir Welded Joint through XFEM method (Fracture and Structural Integrity, 2018)
In fracture mechanics (domain of cracked environments), it is concerned to forecast the behavior of the structures until their ruin.Friction Stir Welding (FSW) is a new process for solid-state joining, it can weld high strength aluminum alloys from the 2000 series.However, despite the research work carried out on the FSW process, the performance and knowledge of the mechanical strength of these welded joints remains limited. At this stage, a local analysis of each zone constituting a welded joint 2024T351 by FSW is carried out. We resort to the numerical simulation of the crack propagation in this joint is used in order to extend the mechanical integrity of this joint with a view to the numerical determination of the crack parameters that are the integral J and the stress intensity factor in each area of joint, in the presence of plasticity under the assumption of proportional loading.We insist on the coherent cohesive zone model in the frame of the XFEM extended finite element method.The numerical results showed that the evaluation of the global two-parameter approach to fracture mechanics in an FSW-welded structure makes it possible to evaluate the impact of the process on the failure of these FSW zones.
Keywords: Friction stir welding; X-fem; Crack propagation; Stress intensity factor; J integral